POTENSI DUA BELAS WISATA PESISIR DAN STRATEGI CITY BRANDING JAKARTA UTARA - Nurkhalila Fajrini (Jurnal Komunikasi dan Bisnis, 2019)
North Jakarta is the capital of DKI Jakarta which potential in tourism. This study discusses what efforts have been made by the government in optimizing the tourism potential, as well as the strategies that can be done to optimize the tourism potential in supporting the formation of North Jakarta city branding. This research was conducted using a qualitative approach. Data were obtained through interviews and documentation studies. The study found that the North Jakarta branding strategy refers to the branding framework stated by Kavartiz (2004). The strategies were done by reviewing the vision and tactics related to branding the city as the â€˜gateway to the Betawi cultureâ€™. Another step of branding strategy was making collaboration among stakeholders to create good cooperation. The activities of city branding involve residents, entrepreneurs and business people in developing and delivering the brand. In the future, we suggest providing public space that represents the brand of North Jakarta as a gateway to the Betawi culture.Keyword: City Branding, Twelve Coastal Tourism, Jakarta UtaraÂ